POTENTIAL ANTIFUNGAL ACTIVITY OF ESSENTIAL OILS AND THEIR APPLICATION IN FOOD PRESERVATION - Tomar, Rajesh Singh; Sharma, Bhawna; Kaushik, Shuchi; Mishra, Raghvendra Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The quality of food is highly affected by different types of biological, chemical, and physical contaminants. Microbial contaminations that are transferred through direct or indirect pathways such as through saliva, pest droppings, blood, or fecal matter affect the quality of food worldwide. Food can be spoiled by bacteria as well as fungus. The fungal microbes secrete toxins to intoxicate the food material rendering it unfit for consumption. The objective of the present review is to explore the application of essential oil (EO) as potent antifungal agent and thus good sources of food preservative. We have reviewed previously published papers on antimicrobial activity of EOs. The antimicrobial activity of these natural plant products has been assayed by different approaches. Apart from their activity against microbes, the other beneficial effects of these plant products such as antioxidant activity and enhancing the food quality are also observed by various groups of scientists all over the globe. On the basis of results obtained by different researchers worldwide, the EOs can be authenticated as a food preservative. For the preservation of food, several chemicals are being used by different food industries at large scale; however, they have some limitations. Recently much attention has been directed toward the development of less or negligibly toxic ethno-products which may be utilized for human use for several purposes such as food preservatives, in cosmetics, and medicines. The plant-based volatile EOs and non-volatile secondary metabolites have wide applications in dietary supplements, food flavoring and preservation, folk medicine, and fragrance industry. Several reports have confirmed the antioxidant efficacy of plant-based EOs in vitro and in vivo. Application of plant materials as dietary supplements and preservatives is mainly due to their antioxidant, antimicrobial, and other biological as well as pharmaceutical potentials. Nowadays, EOs and their components are gaining increased attention because of their relatively safe status, their wide acceptance by consumers and the possibility of their exploitation for potential multipurpose uses. It will be relevant to extract EOs, since these extracted oils may have antimicrobial potential which can be utilized for their possible roles against food spoilage microbes.